Analysis of saliva composition in patients with burning mouth syndrome (BMS) by FTIR spectroscopy - Rodrigues, Laís Morandini [UNESP]; Magrini Alva, Taciana Deprá; da Silva Martinho, Herculano; Almeida, Janete Dias [UNESP] (Elsevier, 2019)
This study was performed to evaluate possible changes in saliva composition at the molecular level that can be associated with burning mouth syndrome (BMS). Saliva samples were collected from 14 women with BMS to be analyzed by FT-IR spectroscopy. The control group (CG) was composed of 14 women who presented similar ages, medical histories and use of medications. The results revealed bands related to proteins in the range 1160-1647 cm −1 and lipids in the range 2852-2922 cm −1 . All bands showed the same or high intensity for the control group, except for the bands at 868 cm −1 and 2058 cm −1 , which corresponded respectively to nucleic acids and thiocyanate and showed great intensity for patients with BMS. Analysis of the data obtained by FTIR spectroscopy allowed us to conclude the presence of alterations in saliva composition that may be directly related to BMS symptomatology, as well as secondary symptoms reported by individuals.
Keywords: Burning mouth syndrome; Diagnosis; Fourier transform- infrared spectroscopy; Saliva